Characteristics of CVA16 B1c strains isolated for the first time in the Heilongjiang Province of China - Yang, Tingting; Sun, Qiang; Liu, Hui; Yang, Ming; Chen, Shuhong; Sun, Wei; Xu, Jun; Yan, Dongmei; Zhu, Shuangli; Han, Zhenzhi; Xiao, Jinbo; Lu, Huanhuan; et al. (Frontiers in Microbiology, 2025)
Hand, foot, and mouth disease (HFMD) represents a globally prevalent infectious disease that is caused by enteroviruses. Enterovirus A71 (EV-A71), coxsackievirus A16 (CVA16), and coxsackievirus A6 (CVA6) are recognized as the predominant causative agents of HFMD. CVA16 is a member of the genus Enterovirus within the family Picornaviridae. B1a and B1b are the most prevalent subgenotypes, whereas the B1c subgenotype is relatively scarce. In this study, a comprehensive analysis was conducted on 15 of CVA16 B1c strains isolated from samples of patients diagnosed with HFMD in Jixi (Heilongjiang Province, China) in 2022. Subsequently, whole genome sequencing of these strains was carried out. Phylogenetic origin and potential recombination events were analyzed by aligning sequences of isolated of CVA16 B1c strains with related sequences deposited in GenBank. The CVA16 B1c isolates examined in this study exhibited a high degree of similarities. Specifically, the nucleotide similarity within the VP1 region ranged from 99.6 to 100%. The average nucleotide substitution rate of CVA16 B1c viruses worldwide was estimated to be 5.14 × 10−3 (4.13–6.27 × 10−3) substitution/site/year, and the most recent common ancestor could be traced back to 2003. The earliest CVA16 B1c strain isolated in China was traced back to 2011. Transmission pathway analysis suggested that Chinese strains may have originated in India. Recombination analysis showed that CVA16 B1c strains likely undergone recombination events with EV-A71 and CVA4. In conclusion, the analysis of a cluster of CVA16 B1c cases detected for the first time in Heilongjiang Province not only expanded the gene sequence library of CVA16 B1c strains in China but also offered an epidemiological basis for further investigations into the antigen–antibody interactions and pathogenicity of CVA16 B1c.